Teaching Happiness to Teachers - Development and Evaluation of a Training in Subjective Well-Being - Rahm, Tobias; Heise, Elke (Frontiers in Psychology, 2019)
Teachers’ health is a persistent challenge for educational systems all over the world. Moreover, research results - especially in the domain of positive psychology – indicate that high levels of well-being are associated with additional benefits improving teachers’ professional performance. Therefore, a training to foster subjective well-being with one training day, two booster sessions and exercises before, during and after the meetings was developed. It consisted of about ten hours of face-to-face time and about three hours for the exercises in total over a five-week training period. Main contents were conditions and consequences of positive and negative emotions and well-being, emotion regulation, time management, savoring and gratitude and the application of positive psychological interventions (like Three Good Things). Analyses of planned contrasts by means of a waiting control group design with three measurement points (pre, post, and follow-up) showed a significantly higher increase for the training group (n = 42) than for the control group (n = 47) in the frequency of positive emotions, life satisfaction and flourishing (interaction effects d = 0.44, d = 0.31 and d = 0.32) and a significantly stronger decrease in the frequency of negative emotions, perceived stress, and experiencing emotional exhaustion (interaction effects d = 0.69, d = 0.51 and d = 0.47) from pre to 1-month follow-up. Training effects were also visible up to five months, although no control group could be realized for this period due to the field approach.